Runx2‐I is an Early Regulator of Epithelial–Mesenchymal Cell Transition in the Chick Embryo. Issue 3 (19th July 2017) - Tavares, Andre L.P.; Brown, Jessie A.; Ulrich, Emily C.; Dvorak, Katerina; Runyan, Raymond B.
Abstract : Background: Although normally linked to bone and cartilage development, the Runt‐related transcription factor, RUNX2, was reported in the mouse heart during development of the valves. We examined RUNX2 expression and function in the developing avian heart as it related to the epithelial–mesenchymal transition (EMT) in the atrioventricular canal. EMT can be separated into an activation stage involving hypertrophy and cell separation and an invasion stage where cells invade the extracellular matrix. The localization and activity of RUNX2 was explored in relation to these steps in the heart. As RUNX2 was also reported in cancer tissues, we examined its expression in the progression of esophageal cancer in staged tissues.Results: A specific isoform, RUNX2‐I, is present and required for EMT by endothelia of the atrioventricular canal. Knockdown of RUNX2‐I inhibits the cell–cell separation that is characteristic of initial activation of EMT. Loss of RUNX2‐I altered expression of EMT markers to a greater extent during activation than during subsequent cell invasion. Transforming growth factor beta 2 (TGFβ2) mediates activation during cardiac endothelial EMT. Consistent with a role in activation, RUNX2‐I is regulated by TGFβ2 and its activity is independent of similarly expressed Snai2 in regulation of EMT. Examination of RUNX2 expression in esophageal cancer showed its upregulation concomitant with the development of dysplasia and continued expression in adenocarcinoma.Conclusions: These data introduce the RUNX2‐I isoform as a critical early transcription factor mediating EMT in the developing heart after induction by TGFβ2. Its expression in tumor tissue suggests a similar role for RUNX2 in the EMT of metastasis. Developmental Dynamics 247:542–554, 2018 . © 2017 Wiley Periodicals, Inc. Key Findings: The transcription factor RUNX2‐I is present in the developing heart and is required for the activation step of epithelialmesenchymal transition in this tissue. RUNX2‐I expression is regulated by TGFB2, similarly to SNAI2 but the activities of these two transcription factors, as shown by knockdown, appear to be independent. An examination of a esophageal carcinoma, known to be mediated by TGFB, shows an expression pattern for RUNX2 that is consistent with an early role in the EMT associated with metastasis.